The trauma and the triumph : gender and partition in eastern India - Bagchi, Jasodhara; Dasgupta, Subhoranjan (Kolkata : Stree ; Mumbai : Distributed by Popular Prakashan, 2003)
Contributed articles on the sufferings of women during the partition of Bengal in 1947; includes personal narratives.
Includes bibliographical references and index.
Keywords: WOMEN -- INDIA -- BENGAL -- HISTORY; BENGAL (INDIA) -- HISTORY -- PARTITION, 1947.